Genomic consequences of intensive inbreeding in an isolated wolf population. Issue 1 (January 2018) - Kardos, Marty; Åkesson, Mikael; Fountain, Toby; Flagstad, Øystein; Liberg, Olof; Olason, Pall; Sand, Håkan; Wabakken, Petter; Wikenros, Camilla; Ellegren, Hans
Abstract Inbreeding (mating between relatives) is a major concern for conservation as it decreases individual fitness and can increase the risk of population extinction. We used whole-genome resequencing of 97 grey wolves (Canis lupus ) from the highly inbred Scandinavian wolf population to identify 'identical-by-descent' (IBD) chromosome segments as runs of homozygosity (ROH). This gave the high resolution required to precisely measure realized inbreeding as the IBD fraction of the genome in ROH (F ROH ). We found a striking pattern of complete or near-complete homozygosity of entire chromosomes in many individuals. The majority of individual inbreeding was due to long IBD segments (>5 cM) originating from ancestors ≤10 generations ago,  with 10 genomic regions showing very few ROH and forming candidate regions for containing loci contributing strongly to inbreeding depression. Inbreeding estimated with an extensive pedigree (F P ) was strongly correlated with realized inbreeding measured with the entire genome (r 2  = 0.86). However, inbreeding measured with the whole genome was more strongly correlated with multi-locus heterozygosity estimated with as few as 500 single nucleotide polymorphisms, and withF ROH estimated with as few as 10, 000 single nucleotide polymorphisms, than withF P . These results document in fine detail the genomic consequences of intensive inbreeding in a population of conservation concern. Whole-genome resequencing of 97 wolves from a highly inbred population reveals complete homozygosity of entire chromosomes in many individuals and characterizes the genomic consequences of intensive inbreeding.